Reduced Circulating Regulatory T Cells in Autoimmune and Chronic Idiopathic Neutropenia of Childhood: An Observational Study of Clinical and Laboratory Associations - Konstantina Toutoudaki; Elena E. Solomou; Marianna Tzanoudaki; Stavros Glentis; Panagiota Perari; Panagiota Davoulou; Eftichia Theodoropoulou; Polyxeni Delaporta; Eleni Stamou; Irene Mavroudi; Charalambos Pontikoglou; Helen Papadaki; et al. (European Journal of Haematology, 2026)
ABSTRACT Objectives To investigate circulating regulatory T cells (Tregs) in children with autoimmune neutropenia (AIN) and chronic idiopathic neutropenia (CIN) and evaluate their associations with clinical and laboratory features of neutropenia. Methods Plasma and Peripheral Blood Mononuclear Cells (PBMCs) were collected from 69 participants. Anti‐neutrophil antibody testing included flow cytometry Granulocyte Immunofluorescence Testing (fGIFT) and Granulocyte Agglutination Testing (GAT). Subjects were classified as AIN upon positive assays ( n = 40), CIN upon negative assays ( n = 19), and controls healthy children ( n = 10). Personal history, infection susceptibility, and laboratory tests were recorded. Tregs were measured through flow cytometry, while FOXP3 expression was measured through Western blot. Results Tregs percentages (Tregs%) and absolute values were significantly lower among AIN and CIN than controls (Tregs%: p < 0.01 for AIN CIN, Tregs: p < 0.01 for AIN, p = 0.01 for CIN‐ Mann‐ Whitney U test). FOXP3 expression was maintained. Tregs were analogous with white blood cells (ρ = 0.43, p < 0.01 Spearman's) and lymphocytes ( ρ = 0.42, p < 0.01) among children with AIN, while Tregs levels were associated infection severity among children with CIN. Conclusions Children with AIN and CIN exhibit reduced circulating Tregs, while these values are associated with clinical and laboratory aberrations, suggesting a potential contribution in the immunopathogenesis of neutropenia.